Volume 2C: Turbomachinery 2015
DOI: 10.1115/gt2015-43141
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Performance and Flow Field of a Centrifugal Compressor Under Negative Pre-Swirl

Abstract: In the paper the effect of negative pre-swirl on the performance and the flow in a centrifugal compressor stage are investigated by both the experimental and numerical methods. The results show that, at a negative pre-swirl, whether the pressure ratio of compressor is increased or not is determined by the contest between the increased energy transfer and flow losses. At a large negative pre-swirl, the flow losses in the IGV and the impeller are increased obviously, which makes the pressure ratio and efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The yþ values near the solid wall were controlled below 10 (Figure 6(b)), because the results presented that the couple of the S-A model and the yþ value within this range had the ability to properly capture the flow characteristics in the boundary layer of blade. 23 It has been shown the previous results that the domain-scaling method may overestimate the intensity of the impeller-diffuser interaction. 16 The study used the full-annulus model to eliminate the error Figure 5.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…The yþ values near the solid wall were controlled below 10 (Figure 6(b)), because the results presented that the couple of the S-A model and the yþ value within this range had the ability to properly capture the flow characteristics in the boundary layer of blade. 23 It has been shown the previous results that the domain-scaling method may overestimate the intensity of the impeller-diffuser interaction. 16 The study used the full-annulus model to eliminate the error Figure 5.…”
Section: Methodsmentioning
confidence: 95%
“…Our previous researches revealed that this method is helpful to the convergence of an unsteady calculation. 23 For the unsteady simulation, the convergence was judged by the following rules: (1) according to the steady solution, the RMS residuals should fall below 10 À3 ;…”
Section: Methodsmentioning
confidence: 99%
“…This technology achieves the goal of widening the margin of stable operation and improving the compression efficiency of centrifugal compressors by adjusting the angle of the inlet guide vanes and thus changing the pre-rotation angle of the gas entering the compressor. Zhao et al [7] investigated the effects of VIGVs in negative pre-swirls on the performance and internal flow of centrifugal compressors, respectively. A. et al [8] discussed the aerodynamic effects of precession vortices generated by IGV regulation on the compressor.…”
Section: Introductionmentioning
confidence: 99%
“…Vogel, Abhari, and Zemp (2014) indicated that with an increase in the flow coefficient, the pressure fluctuation amplitude decreases in the diffuser passage. Zhao et al (2015) employed CFD techniques to analyze the interaction of the inlet guide vane and the impeller, observing two loading peaks at the impeller blade leading edge for a small mass flow coefficient during a passage cycle.…”
Section: Introductionmentioning
confidence: 99%